Rapidly Progressive Spontaneous Spinal Epidural Abscess - Abdurrahman Aycan; Ozgür Yusuf Aktas; Feyza Karagoz Guzey; Azmi Tufan; Cihan Isler; Nur Aycan; İsmail Gulsen; Harun Arslan (Case Reports in Infectious Diseases)
Spinal epidural abscess (SEA) is a rare disease which is often rapidly progressive. Delayed diagnosis of SEA may lead to serious complications and the clinical findings of SEA are generally nonspecific. Paraspinal abscess should be considered in the presence of local low back tenderness, redness, and pain with fever, particularly in children. In case of delayed diagnosis and treatment, SEA may spread to the epidural space and may cause neurological deficits. Magnetic resonance imaging (MRI) remains the method of choice in the diagnosis of SEA. Treatment of SEA often consists of both medical and surgical therapy including drainage with percutaneous entry, corpectomy, and instrumentation.